2021
DOI: 10.1093/jamia/ocab011
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing physician EHR use with vendor derived data: a feasibility study and cross-sectional analysis

Abstract: Objective To derive 7 proposed core electronic health record (EHR) use metrics across 2 healthcare systems with different EHR vendor product installations and examine factors associated with EHR time. Materials and Methods A cross-sectional analysis of ambulatory physicians EHR use across the Yale-New Haven and MedStar Health systems was performed for August 2019 using 7 proposed core EHR use metrics normalized to 8 hours of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
63
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 44 publications
(64 citation statements)
references
References 37 publications
1
63
0
Order By: Relevance
“…In an era of increasing EHR use measurement and optimization, it is important to examine the factors affecting academic otolaryngologist EHR use. 16 This study examined the relationship between resident coverage in clinic and attending otolaryngologist EHR use. Increasing resident clinic coverage was significantly associated with reduced attending EHR use, with much of this reduction appearing to be due to assistance with note writing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In an era of increasing EHR use measurement and optimization, it is important to examine the factors affecting academic otolaryngologist EHR use. 16 This study examined the relationship between resident coverage in clinic and attending otolaryngologist EHR use. Increasing resident clinic coverage was significantly associated with reduced attending EHR use, with much of this reduction appearing to be due to assistance with note writing.…”
Section: Discussionmentioning
confidence: 99%
“…11,15 A new field of EHR use measurement is developing as a means of improving EHR workflow, as well as measuring clinician efficiency and productivity. 16 One avenue to better understand clinician EHR use is analyzing the data, timestamps, and logs automatically collected by many electronic systems. 11,14,17,18 The international EHR vendor Epic (Epic Systems Corporation, Verona, Wisconsin) collects data on user interactions with the EHR, which is compiled into a provider efficiency profile (PEP).…”
Section: Introductionmentioning
confidence: 99%
“…12,13 Time motion studies and EHR log records have indicated an increase in time allocated for desktop medicine with physicians spending nearly 2 hours in the EHR and on other desk work for every hour of direct patient care. 11,[14][15][16][17][18] This perhaps contributes to overflow of EHR work into the physician's nonclinical and personal time, negatively affecting work-life balance. 19 There is accumulating evidence indicating the association of EHR use after work hours with occupational distress including burnout.…”
Section: Background and Significancementioning
confidence: 99%
“…24 Five of these metrics could be implemented for ambulatory, nonteaching physicians in 2 health care systems operating different EHR vendor products. 22 To our knowledge, no previous studies have examined physician productivity and EHR use patterns and their association with physician turnover. Therefore, we conducted a study of ambulatory physicians' turnover across an ambulatory care delivery network over a 2-year period to determine the association of physicians' productivity and EHR use patterns with departure.…”
Section: Introductionmentioning
confidence: 99%